Artikel Ilmiah PLP Universitas Sultan Ageng Tirtayasa Dampak Program Gerakan Literasi Sekolah (GLS) dalam Meningkatkan Minat Baca Peserta Didik di MAN 1 Pandeglang - Ninda Kiyan Maharani; Aulia Zahra Yuanita; Yana Apriyanti; Sundawati Tisnasari (Jurnal Bintang Pendidikan Indonesia, 2025)
This research discusses the impact of the School Literacy Movement (GLS) at MAN 1 Pandeglang to increase students' interest in reading and literacy skills through literacy outreach every Wednesday morning. The method used is descriptive qualitative, with data collection through interviews, observation and documentation. The results show that GLS is implemented in three stages: Habituation, Development, and Learning. Even though there is support from various parties, challenges such as a lack of reading materials and the performance of the school literacy team are obstacles. This research recommends improving facilities and program evaluation to support the success of GLS. With that, the writing of this article will discuss the problem statement: 1) What is the meaning of the School Literacy Movement (GLS) 2) How is the School Literacy Movement (GLS) implemented. 3) What is the impact of the Literacy program on MAN 1 Pandeglang students and students?